Analisis Waqf Management Tahun 2018-2022 Menggunakan Pendekatan Bibliometrik - Amanda, Rezka Yoli (ITB AAS INDONESIA Surakarta, 2023)
Waqf management is a process of planning, organizing, leading and supervising nazhir to achieve community welfare goals. This study uses bibliometric analysis using data obtained from Google Scholar with the aim of knowing the development of research on waqf management using a blibiometric approach. The results showed that there were 77 articles related to waqf management in 2018-2022. Based on the results of data visualization, it was found that there was a high growth in publications, where the majority of articles were published in 2022. The increasing number of articles on waqf management shows the importance of good waqf management for nadzirs. In network visualization, articles on waqf management consist of four clusters with 9 keywords including waqf management, risk management, waqf institutions, challenges, productive waqf, waqf land, waqf poverty, cash waqf, waqf assets with a total of 349 citations.